Analisis Pengelolaan Keuangan Daerah Terhadap Akuntabilitas Kinerja Pemerintah Kabupaten Boalemo - Kadjintuni, Zulaiha; Tontik, Deysi; Darman, Darman; Rachman, Azis; Dunggio, Titin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This research was conducted to analyze the role of regional financial management including budget planning, budget execution, budget reporting/accountability and evaluation of performance accountability of the local government of Boalemo Regency. This research method uses quantitative research with an observation process. The results of the study show that budget planning, budget execution, budget accountability and budget evaluation have a significant effect on the performance accountability of the Boalemo District Government. In terms of financial management, especially in terms of budget planning to focus more on budgets that support the agreed program and performance targets.